Cork as a new (green) coating for solid-phase microextraction: Determination of polycyclic aromatic hydrocarbons in water samples by gas chromatography–mass spectrometry - Dias, Adriana Neves; Simão, Vanessa; Merib, Josias; Carasek, Eduardo (Analytica Chimica Acta, 2013)
A new fiber for solid-phase microextraction (SPME) was prepared employing cork as a coating. The morphology and composition of the cork fiber was evaluated by scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR), respectively. The proposed fiber was used for the determination of polycyclic aromatic hydrocarbons (PAHs) in river water samples by gas chromatography–selected ion monitoring–mass spectrometry (GC–SIM–MS). A central composite design was used for optimization of the variables involved in the extraction of PAHs from water samples. The optimal extraction conditions were extraction time and temperature of 60 min and 80 °C, respectively. The detection and quantification limits were 0.03 and 0.1 μg L−1, respectively. The recovery values were between 70.2 and 103.2% and the RSD was ≤15.7 (n = 3). The linear range was 0.1–10 μg L−1 with r ≥ 0.96 and the fiber-to-fiber reproducibility showed RSD ≤ 18.6% (n = 5). The efficiency of the cork fiber was compared with commercially available fibers and good results were achieved, demonstrating the applicability and great potential of cork as a coating for SPME.
Keywords: Cork; GC–MS; PAHs; Solid-phase microextraction; Water samples